PENGARUH MOTIVASI KERJA DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI PADA BALAI BESAR METEOROLOGI, KLIMATOLOGI, DAN GEOFISIKA WILAYAH II KOTA TANGERANG SELATAN - Ivan Valda Fadhila; Chotamul Fajri (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of work motivation and job training on employee productivity either partially or simultaneously. This research was conducted using quantitative research methods involving employees as samples in this study. Also, this study uses various research tests, namely validity test, reliability test, classical assumption test, correlation coefficient test, regression coefficient test, coefficient of determination test, t test and f test. The result of this research is that on the work motivation variable, the regression equation Y = 19,948 + 0,532 is obtained. The value of the work motivation regression coefficient (X1) is 0,532, this number is positive, it means that if the constant is fixed and there is no change in the work motivation variable data (X1), then every 1 unit change in the work motivation variable (X1) will result in an increase in productivity (Y) of 0.532. Then, on the job training, the regression equation can be obtained Y = 8,626 + 0,799 X2, where X2 = Job training. The coefficient value is 0.799 (positive), which shows a unidirectional effect, meaning that if job training is increased by one, it will increase employee productivity by 8.626. Then, on employee productivity, the multiple regression equation Y = 8,381 + 0,057 X1 + 0,751 X2 + e. The value of the regression coefficient on the productivity variable is 8.381, concluding that if the Work Motivation (X1) and Job Training (X2) remain (no change) then the consistency value of Productivity (Y) is 8.381. The statistical results of the t test have a positive and significant effect on work facilities on employee productivity. Based on the table that t count t hitung 12,228 > t tabel 1,989 or significant 0.000 <0.05, thus Ha is accepted and Ho is rejected, so that partially there is a positive and significant effect of work motivation on employee productivity. Then, the statistical results of the t test have a positive and significant effect on job training on employee productivity. Based on the table that t count t hitung 12,228 > t tabel 1,989 and significant 0.000 < 0.05, thus Ha is accepted and Ho is rejected, so that partially there is a positive and significant effect of job training on employee productivity. And, the results of statistical calculations show the calculated F hitung 74,560 > F tabel 3,095. by using a significance limit of 0.05, the significance value obtained is 0.000 < 0.05. This means that the hypothesis which states that the simultaneous variable work motivation, job training, has an influence on employee productivity.